Microfluidic based multiplex qRT-PCR identifies diagnostic and prognostic microRNA signatures in sera of prostate cancer patients - Moltzahn, Felix (2010)
Recent prostate specific antigen (PSA) based screening trials indicate an urgent need for novel and non-invasive biomarker identification strategies to improve the prediction of prostate cancer behavior. Non-coding microRNAs (miRNAs) in the serum and plasma have been shown to have potential as non-invasive markers for physiological and pathological conditions. To identify serum miRNAs that diagnose and correlate with prognosis of prostate cancer, we developed a multiplex quantitative reverse transcription PCR (qRT-PCR) method involving purification of multiplex PCR products followed by uniplex analysis on a microfluidics chip to evaluate 384 human miRNAs. Using Dgcr8 and Dicer knockout (small RNA - deficient) mouse ES cells (mESC) as the benchmark, we confirmed the validity of our technique, while uncovering a significant lack of accuracy in previously published methods. Profiling 48 sera from healthy men and untreated prostate cancer patients with differing CAPRA (Cancer of the Prostate Risk Assessment) scores, we identified miRNA signatures that allow to diagnose cancer patients and correlate with prognosis. These serum signatures include oncogenic and tumor suppressive miRNAs suggesting functional roles in prostate cancer progression.